KEEFEKTIFAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE DAN THINK-PAIR-SHARE DALAM PEMBELAJARAN MENULIS DESKRIPSI - Wanggai, Febe Fenny Irawati; Doi, Maksimilianus (IKIP PGRI Pontianak, 2019)
The current study aimed at investigating (1) a significant difference of cooperative models of picture and picture, think-pair-share, and conventional model, (2) the most significant effectiveness of cooperative models of picture and picture, think-pair-share, and conventional model in learning process of descriptive writing at grade X of the students of SMAK Frateran Ndao Ende. This study belonged to quasi-experimental study with randomized control-group pretest-posttest design. 90 students with 30 students in each class were employed as samples using total sampling technique with three intact classes. The data were a non-test method in the form of a descriptive writing assignment. The data were analyzed using one-way ANOVA continued by Scheffe test. The upshots of the study denote that (1) there is a significant difference of cooperative models of picture and picture, think-pair-share, and conventional model in the learning process of descriptive writing with F=140.578, and a significant value of p<0.05, (2) cooperative model of think-pair-share is the most effective type in the learning process of descriptive writing.